Need of Capacity Building of Teachers on Learning Outcomes - Yadav, Kiran; Paul, Devasish; Baruah, Runjun (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Education is a social institution and is subject to change in response to social dynamics because the teacher can provide the much needed quality control devices through student assessment. He or she can be seen as the manager, motivator or at best, the managing director and chief executive officer of the educational system. The most meaningful information for improving instruction and providing clear and useful feedback to learners is collected daily in the classroom through classroom assessment of the learners. There is a direct relationship between appropriate classroom assessment techniques and higher student achievement, to the extent that when practiced effectively, can improve students learning. The academic imperative is for teachers to renovate their professional competence and capacity to be able to respond to the dynamics of classroom assessment. Therefore this paper discusses about the concept of learning outcomes, origin of learning outcomes, pillars of teachers‟ capacity in improving learning outcomes, need of capacity building of teachers‟ on learning outcomes etc. It also recommended among others, the training and retraining of teachers on newer method or techniques of classroom assessment and teachers sharing ideas with peers through teacher moderation.